The aggressive child. (7th October 2018) - Scott, James G; Tunbridge, Michael; Stathis, Stephen
Abstract: Aggression in children is a common transdiagnostic symptom associated with a wide range of developmental and mental health problems. It emerges early and without intervention, may increase in severity as the child grows stronger. Aggressive children are more likely to experience physical and mental illness, unemployment, poverty and forensic problems as adults. Strategies to prevent aggression must address risk factors: low maternal education, adolescent pregnancy, in utero exposure to tobacco and alcohol, poverty, coercive parenting, childhood maltreatment and bullying victimisation. The aggressive child requires a comprehensive assessment to identify and manage underlying or comorbid problems, to understand the reasons for the aggressive behaviour and to detect modifiable factors that exacerbate or perpetuate the aggression. Psychosocial interventions include parenting skills training and child‐directed cognitive behavioural therapy, whereas pharmacotherapy may be used to treat underlying developmental or mental health problems or to manage the aggression.